EFEKTIVITAS PELATIHAN “MATH AND ME” BERLANDASKAN PRINSIP ATTRIBUTIONAL FEEDBACK DALAM MENINGKATKAN KONSEP DIRI AKADEMIS - Monica Gunawan; Sri Tiatri; Sesilia Monika (Provitae: Jurnal Psikologi Pendidikan, 2016)
Previous research showed that attributional feedback could enhance academic self-concept in targeted subject. However, research in Indonesia about intervention to academic self-concept is still limited (Wahyuningsih, 2010) and had been done with special need participants (Tarmidi & Akbar-Hawidi, 2009). This research aimed to test the effectiveness of “Math and Me” training based on attributional feedback in enhancing academic self-concept, especially on mathematic subject among grade 7 student at Junior High School. The participants of this research were 3 students in grade 7 with low score of academic self-concept. The research design was one group pretest-posttest design. Pretest-posttest conducted on academic self-concept scores. Based on data analysis, academic self-concept scores significantly enhance after training. Participants also show more positive attitude, such as more open and actively involved in the mathematic learning processes. The result indicates that “Math and Me” training based on attributional feedback is effective in enhancing academic self-concept, especially on mathematic subject among grade 7 student at junior high school.Keywords: "Math and Me” training with attributional feedback, academic self-concept